Molecular characterization of hepatitis B virus X gene in chronic hepatitis B patients - Barbini, Luciana Fernanda (2012)
Background: HBV-X protein is associated with the pathogenesis of HBV related diseases, specially in hepatocellular carcinomas of chronic patients. Genetic variability of the X gene includes genotypic specific variations and mutations emerging during chronic infection. Its coding sequence overlaps important regions for virus replication, including the basal core promoter. Differences in the X gene may have implications in biological functions of the protein and thus, affect the evolution of the disease. There are controversial results about the consequences of mutations in this region and their relationship with pathogenesis. The purpose of this work was to describe the diversity of HBV-X gene in chronic hepatitis patients infected with different genotypes, according to liver disease. Methods. HBV-X gene was sequenced from chronic hepatitis B patient samples, analyzed by phylogeny and genotyped. Nucleotide and aminoacid diversity was determined calculating intragenetic distances. Mutations at 127, 130 and 131 aminoacids were considered in relation to liver disease. Results: The most prevalent genotype detected in this cohort was F (F1 and F4), followed by D and A. Most of the samples corresponding to genotypes A and F1 were HBeAg(+) and for genotypes D and F4, HBeAg(-) samples were represented in a higher percentage. Intragenetic distance values were higher in HBeAg(-) than in positive samples for all genotypes, and lower in overlapped regions, compared to single codification ones. Nucleotide and aminoacid diversities were higher in HBeAg(-), than in HBeAg(+) samples. Conclusions: Independently of the infecting genotypes, mutations at any of 127, 130 and/or 131 aminoacid positions and HBeAg(-) status were associated with mild liver disease in this cohort.